Faktor – faktor yang Mempengaruhi Persalinan Berdasarkan Umur Kehamilan dengan Menggunakan Analisis Regresi Logistik - Melly Kurniawati; Media Rosha; Nonong Amalita (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – Childbirth is a natural event experienced by a mother. Based on interviews in September 2015 were conducted in the mother house who have experienced childbirth said that the mother gave birth at 29 weeks gestational age infant’s organ is not mature enough, and the baby eventually died. The aim of this study was to determine the form of the logistic regression model, factors that significant and opportunity of the each factors that significantly affect childbirth based on gestational age. The results were obtained form the logistic regression model that describes the factors that affect childbirth based on gestational age. Who the significance factor are history of childbirth, anemia, and hypertension. Opportunity mother had a history of preterm childbirth, anemia, and hypertension the opportunity of the mother will experience premature childbirt is 0.999. Keywords: Childbirth, Logistic Regression, Probability